Vertical judicial dialogues in asylum cases : standards on judicial scrutiny and evidence in international and European asylum law - Baldinger, Dana, 1969- (Leiden ; Boston : Brill Nijhoff, 2015)
What do international and EU law require from the national asylum judge with regard to the intensity of judicial scrutiny to be applied and evidentiary issues? To answer that question, an analysis is made of the provisions on national judicial proceedings contained in the Refugee Convention (RC), the International Covenant on Civil and Political Rights (ICCPR), the UN Convention against Torture (CAT), the European Convention on Human Rights (ECHR), and the EU Charter of Fundamental Rights. In addition, the assessment as performed by the UN Human Rights Committee, the UN Committee against Torture and the European Court of Human Rights in cases concerning the expulsion of asylum seekers is analysed.--
Introduction -- The 1951 convention relating to the status of refugees (RC) and the protocol (RP) relating to the status of refugees -- The 1966 International Covenant on Civil and Political Rights (ICCPR) -- The 1984 Convention against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment (CAT) -- The 1950 European Convention for the Protection of Human Rights and Fundamental Freedoms (ECHR) -- European Union Asylum Law -- National courts and the independent and rigorous scrutiny -- Repeat cases, Dublin cases, fast-track national proceedings.
Includes bibliographical references (pages 503-521) and index.
Keywords: Convention Relating to the Status of Refugees -- (1951 July 28). -- (1967 January 31); International Covenant on Civil and Political Rights -- (1966 December 16); Convention against Torture and Other Cruel, Inhuman, or Degrading Treatment or Punishment -- (1984 December 10); Convention for the Protection of Human Rights and Fundamental Freedoms -- (1950 November 5); Convention against Torture and Other Cruel, Inhuman, or Degrading Treatment or Punishment; Convention for the Protection of Human Rights and Fundamental Freedoms; Convention Relating to the Status of Refugees (1951 July 28); International Covenant on Civil and Political Rights; Asylum, Right of -- European Union countries; Asylum, Right of; Emigration and immigration law -- European Union countries; Emigration and immigration law; Asylum, Right of; Emigration and immigration law; European Union countries